2013
DOI: 10.1007/s10096-013-1982-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of hematopoietic stem cell transplantation from hepatitis B core antibodies-positive donors with low/undetectable viremia in HBV-naïve children

Abstract: Scarce data exist on allogeneic hematopoietic stem cell transplantation (HSCT) outcomes in hepatitis B virus (HBV)-naïve recipients from HBV-experienced donors. Long-term follow-up is herein reported for 17 allogeneic HSCT performed in 13 HBV-naïve children from HBc-antibodies-positive donors between 2006 and 2012. Four donors were HBs-antigen-positive, with detectable but low viremia in 2 cases (<2 log₁₀IU/ml). HBV-DNA was undetectable in all transplanted cell products. Recipients' HBV prophylaxis consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[27] However, the current recommendations by the Turkish Association for the Study of the Liver, Acute Liver Failure and Liver Transplantation Special Interest Group suggest 5000 IU of HBIG should be administered intravenously to lowrisk patients and 10 000 IU should be administered to high-risk patients while NA monoprophylaxis without HBIG administration is not recommended in the early periods following LT. [6] Among HBIG-free protocol, lamivudine monotherapy is associated with the emergence of escape mutation, while lamivudine/adefovir combination had no HBV recurrence at 22-month follow-up. [28] With the advent of more potent antivirals with lower resistance, more patients have undetectable HBV DNA prior to LT, thereby decreasing posttransplant reinfection rates. Similar arguments can be made to explain the variability in prophylactic recommendations in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…[27] However, the current recommendations by the Turkish Association for the Study of the Liver, Acute Liver Failure and Liver Transplantation Special Interest Group suggest 5000 IU of HBIG should be administered intravenously to lowrisk patients and 10 000 IU should be administered to high-risk patients while NA monoprophylaxis without HBIG administration is not recommended in the early periods following LT. [6] Among HBIG-free protocol, lamivudine monotherapy is associated with the emergence of escape mutation, while lamivudine/adefovir combination had no HBV recurrence at 22-month follow-up. [28] With the advent of more potent antivirals with lower resistance, more patients have undetectable HBV DNA prior to LT, thereby decreasing posttransplant reinfection rates. Similar arguments can be made to explain the variability in prophylactic recommendations in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…In statistical analysis there were no significant associations between anti‐HBc and anti‐HBs serostatus and the presence of occult HBV infection. In a study conducted in France 20 there were no cases of HBV infection after allogeneic HSCT from 17 anti‐HBc‐positive donors between 2006 and 2012. The ECIL‐5 has stated that HBsAg‐negative and anti‐HBc‐positive donors might transmit HBV to recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up anti‐HBc assessment in this patient may help to clarify the likelihood of this possibility. Another observation that should be noted was that 7 recipients of 20 anti‐HBc‐positive donors received intravenous immunoglobulin after HSCT, which might help to prevent HBV reactivation 20 . More data are needed to clarify whether anti‐viral prophylaxis is necessary in patients whose donors are anti‐HBc‐positive but HBV viral load is undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, little is known about the effects of anti-HBc-positive donors on HBV-negative HSCT recipients. Recent reports documented the absence of HBV transmission in HBV-naïve children undergoing prophylaxis with vaccination and/or immunoglobulins when receiving HSCs from an anti-HBc-positive donor [45]. Another study demonstrated a protective role of HBV-immune/ exposed HBV donors for anti-HBc-positive HSCT recipients who did not receive LMV prophylaxis [21].…”
Section: Discussionmentioning
confidence: 99%